2013
DOI: 10.1021/nl400558u
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Thermal Conductivity of PbTe Nanocrystal Coated Glass Fibers by the 3ω Method

Abstract: Fiber-based thermoelectric materials can conform to curved surfaces to form energy harvesting devices for waste heat recovery. Here we investigate the thermal conductivity in the axial direction of glass fibers coated with lead telluride (PbTe) nanocrystals using the self-heated 3ω method particularly at low frequency. While prior 3ω measurements on wire-like structures have only been demonstrated for high thermal conductivity materials, the present work demonstrates the suitability of the 3ω method for PbTe n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…Various nanostructures have been theoretically proposed or experimentally demonstrated to have a substantially reduced κ l compared to their bulk counterparts, for example, nanowires 3 , 4 , nanocomposites 5 , 6 , superlattices (SL) 7 , 8 , nanomeshes 9 , 10 , and pillared thin films 11 13 . Typically, the low κ l of the above structures partially or completely stems from the extensive surface and interface scatterings in the nanostructures, which can be understood by the Casimir picture 14 , i.e., classical size effect.…”
Section: Introductionmentioning
confidence: 99%
“…Various nanostructures have been theoretically proposed or experimentally demonstrated to have a substantially reduced κ l compared to their bulk counterparts, for example, nanowires 3 , 4 , nanocomposites 5 , 6 , superlattices (SL) 7 , 8 , nanomeshes 9 , 10 , and pillared thin films 11 13 . Typically, the low κ l of the above structures partially or completely stems from the extensive surface and interface scatterings in the nanostructures, which can be understood by the Casimir picture 14 , i.e., classical size effect.…”
Section: Introductionmentioning
confidence: 99%
“…[17] Recent research has witnessed rapid advances in the synthesis of am yriad of high-quality colloidal nanocrystals. [2,3,6] Among the IV-VI semiconductor nanocrystals,lowband-gap lead chalcogenide NPs are of particular interest as they possess much broader size-tunable optoelectronic properties from the visible to the near-IR region that open up opportunities for their use in solar energy conversion, [18] thermoelectric devices, [19] and photodetectors. [20] It is noteworthy that the synthesis of lead chalcogenide solid NPs,f or example,P bTe, often requires the use of trialkylphosphine ligands (e.g., trioctylphosphine (TOP),t rioctylphosphine oxide (TOPO), and tributyl phosphate (TBP)) because of the poor solubility of tellurium in most organic solvents.…”
mentioning
confidence: 99%
“…According to (8), the value of is dependent on several factors, such as the shape of band structure, chemical potential, and temperature. In fact, it can be shown that converges to a constant value (Sommerfeld limit) of…”
Section: Basics Of Thermoelectric Materialsmentioning
confidence: 99%